Changes in the volatile profile of four cultivars of quince (Cydonia oblonga) produced by codling moth (Cydia pomonella) infestation - Lopez, María Liza; Gomez, María Pía; Díaz, Ariel; Jofré Barud, Flavia; Camina, Julia Laura; Dambolena, José Sebastián (Elsevier, 2022)
The production of quince (Cydonia oblonga Miller) is affected worldwide by codling moth (Cydia pomonella L.), an oligophagous pest. In this study, volatile compounds in healthy and infested fruits were collected from four cultivars of quince: Champion, Portugal, Smyrna and INTA 147. Volatiles were extracted by SPME and analyzed by GC-MS. Up to 30 compounds were identified in the volatile profiles of uninfested quinces, ranging from 90.9% to 98.4% of the total relative abundance. The volatile profile of all four cultivars of quince was similar, with (E, E)-α-farnesene and octanoic acid- ethyl ester as the main components. Infested fruits presented increased levels of (E,E)-α-farnesene, while minor compounds decreased significantly. Champion and Smyrna varieties might be more susceptible cultivars to infestation as their healthy fruits presented the highest contents of (E,E)-α-farnesene and Pear Ester, both codling moth kairomones. The role of these highly recognized kairomones in the chemical ecology of codling moth in quince is discussed.